2021
DOI: 10.1007/s11356-021-13130-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of energy consumption and economic growth on ecological footprint: new evidence from Pakistan

Abstract: This study explores the asymmetric effects of both aggregate and disaggregate forms of energy consumption along with economic growth on environmental quality for Pakistan covering the period from 1971 to 2014. We have employed unit root test with breaks for stationary checks, BDS test for nonlinearity check and nonlinear autoregressive distributed lag (NARDL) approach for assessing the asymmetric co-integrating relationships among the variables by decomposing them into positive and negative shocks. The empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…In the same light, Ali et al (2016b) employed the ARDL on data from Nigeria and settled that energy consumption and economic growth had a positive and statistically significant effect on environmental condition. Meanwhile, Majeed et al (2021) used the nonlinear autoregressive distributive lag technique for the Pakistani economy and concluded that only negative shocks have a significant impact on ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same light, Ali et al (2016b) employed the ARDL on data from Nigeria and settled that energy consumption and economic growth had a positive and statistically significant effect on environmental condition. Meanwhile, Majeed et al (2021) used the nonlinear autoregressive distributive lag technique for the Pakistani economy and concluded that only negative shocks have a significant impact on ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the empirical literature examined, it can be deduced that environmental quality has vastly been measured via CO 2 emission (Ohlan 2015; Altıntaş and Kassouri 2020; Salahuddin et al 2015;Ali et al, 2016a, b Sulaiman and Abdul-Rahim 2018 among others) with very few of this studies making used of broader measures like the ecological Footprint (EF) (Majeed et al 2021;Shittu et al 2021), and even among the few that have used EF, non-have considered the effect of the different economic variables on the available bio capacity to the best of our acknowledge. It becomes apparent to consider a broader measure of environmental quality which will lead to better inference and proper policy recommendations to achieve the sustainable development goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical findings of this paper concerning energy consumption and economic growth are rational and agree with early studies of (Adebayo, 2021;Purnama et al, 2020;Shahbaz et al, 2013) where they found energy consumption and economic growth are the main determinants of environmental degradation. Also, gross capital formation and capital investment play a crucial role to improve environmental quality through decarbonization, environmental sustainability management, and providing environmentally friendly technologies (Bukhari et al, 2014;Majeed et al, 2021;Mesagan et al, 2019). International trade openness enables countries to access modern technology and stimulate foreign direct investment inflow which enhances clean industries.…”
Section: The Diagnostic Tests and Stabilitymentioning
confidence: 99%
“…Mesagan et al (2019) stated that capital investment is a substantial channel to enhance environmental quality through reducing CO2 emissions. The projects of environment-friendly capital formation can back up the government in decarburization projects through managing environmental sustainability with the capital formation of modern technology (Majeed et al, 2021). Gross capital formation would improve environmental quality by providing environmentally friendly technologies for production (Bukhari et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation